The critical role of the Hippo signaling pathway in kidney diseases - Sun, Yuting; Jin, De; Zhang, Ziwei; Jin, Di; Xue, JiaoJiao; Duan, LiYun; Zhang, YuQing; Kang, XiaoMin; Lian, FengMei (Frontiers in Pharmacology, 2022)
The Hippo signaling pathway is involved in cell growth, proliferation, and apoptosis, and it plays a key role in regulating organ size, tissue regeneration, and tumor development. The Hippo signaling pathway also participates in the occurrence and development of various human diseases. Recently, many studies have shown that the Hippo pathway is closely related to renal diseases, including renal cancer, cystic kidney disease, diabetic nephropathy, and renal fibrosis, and it promotes the transformation of acute kidney disease to chronic kidney disease (CKD). The present paper summarizes and analyzes the research status of the Hippo signaling pathway in different kidney diseases, and it also summarizes the expression of Hippo signaling pathway components in pathological tissues of kidney diseases. In addition, the present paper discusses the positive therapeutic significance of traditional Chinese medicine (TCM) in regulating the Hippo signaling pathway for treating kidney diseases. This article introduces new targets and ideas for drug development, clinical diagnosis, and treatment of kidney diseases.